Comparison of caproic acid and monolaurin with zinc oxide and benzoic acid; effect on growth performance of weaned pigs - N. Portocarero (Journal of Applied Animal Nutrition)
Medium chain organic acids (MCOA) offer the potential to replace zinc oxide, without dependence on antibiotic use, and can replace or reduce the use of benzoic acid in pig production. A study was conducted to evaluate the effects of caproic acid (C6) and C12 monolaurin (C12M) on the growth performance of weaned pigs, in comparison with zinc oxide (ZnO) and benzoic acid (BA). Specifically, the trial examined whether MCOA, at a reduced inclusion level of BA, could maintain performance levels of pigs similar to those receiving a higher inclusion level of BA. In total, 240 pigs from weaning until 27 d post-weaning were used in a completely randomised block trial with six treatments and eight replicate pens per treatment. Treatments were: (1) control (CON), basal diet (BD); (2) BD+ZnO (ZnO); (3) BD+5,000 mg/kg BA (BA); (4) BD+2,500 mg/kg BA+2,000 mg/kg C12M+700 mg/kg C6 (BAlow/MCOA); (5) BD+2,000 mg/kg C12M+700 mg/kg C6 (MCOA); (6) BD+1000 mg/kg C12M+700 mg/kg C6 (MCOAlow). Feed and water were provided ad libitum. Pigs receiving BA or BA low/MCOA had improved feed conversion ration (FCR) during the period 0-14 days, compared with control pigs (1.02 vs 1.17, P<0.05; 1.06 vs 1.17; P=0.084, respectively). The FCR of pigs receiving BAlow/MCOA was similar to those receiving BA at the higher inclusion-level. Pigs showed good health throughout the study, as indicated by clinical and faecal scores. Replacement of ZnO was inconclusive and further studies with more challenging health conditions are required to conclude benefits.